ANALISIS REDAMAN PELAT VERTIKAL BAWAH LAUT PADA STRUKTUR LEPAS PANTAI TIPE SPAR - Hidayatullah - (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
A spar platform is an offshore structure or building with a mooring system with structural damping forces and natural periods beyond the reach of waves. In general, a spar is a large floating cylindrical structure with a fairly large and deep draft. The spar itself is used to assist the drilling process and offshore crude oil production. The buoyancy of the Spar itself is used to support activity facilities that are above the water surface. In the spar structure, it is necessary to add a foot attached to the pile foundation on the seabed using tendons or tethers to increase stability in degrees of freedom of slope and roll. This research is a development research in determining the attenuation of the vertical plate against the tilt movement.